Długa droga donikąd. O Sydneya Shoemakera funkcjonalistycznej teorii tożsamości osobowej - HENSEL, Witold M. (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
The paper presents and criticizes Sydney Shoemaker’s account of personal identity. Briefl y stated, Shoemaker’s theory says that personal identity over time consists in psychological continuity, unless there has been branching involved. The fi rst three sections describe the standard construal of the problem and recount how Shoemaker developed his theory from Locke’s memory theory. Section 4 discusses how functionalism is supposed to shed light on the notion of personal identity, and section 5 gives a short summary of the theory’s shortcomings. I argue that: (1) Shoemaker’s defi nition of psychological continuity is elliptical and, thus, has no bearing on the puzzling borderline cases most theories of personal identity attempt to handle; (2) Shoemaker’s theory lacks explanatory value, because its functionalist framework relies for content on a non-existent psychological theory; (3) the functionalist framework is at odds with the formal constraint of transitivity Shoemaker, like most authors, sets on the notion of personal identity; and (4), appearances to the contrary notwithstanding, Shoemaker’s theory is not concerned with the nature of personal identity, but with one of its several concepts, which is to say that, treated as a metaphysical account, it is simply a collection of unjustifi ed claims about the mind.